1991
DOI: 10.1016/0014-5793(91)80994-e
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease activity and substrate preference of human eosinophil cationic protein (ECP)

Abstract: The eosinophil cationic protein (ECP), a potent helminthotoxin with considerable ncurotoxic activity, was recently shown to also have ribonucleolytic activity. In this work the substrate preference of ECP ribonuclcase action was studied in detail. With singe-stranded RNA or synthetic polyribonucleotide substrates ECP showed significant but low activity, 70. to 200-fold less than that of bovine RNase A. ECP hydrolyzed .RNA more rapidly than it did any synthetic polynucleotide. Poly(U) was degraded more rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…Early kinetic studies on the RNase activity of ECP indicated a pyrimidine specificity for the base position at the active site with a slight preference for cytidine in substrates of low mo-lecular mass but a clear preference for polyuridylic acid (poly(U)), in comparison with polycytidylic acid (poly(C)) (18,19). No activity toward either 2Ј,3Ј-phosphate cyclic mononucleotides, dinucleoside monophosphates, or double-stranded RNA was detected (20).…”
Section: Human Eosinophil Cationic Protein (Ecp)mentioning
confidence: 99%
“…Early kinetic studies on the RNase activity of ECP indicated a pyrimidine specificity for the base position at the active site with a slight preference for cytidine in substrates of low mo-lecular mass but a clear preference for polyuridylic acid (poly(U)), in comparison with polycytidylic acid (poly(C)) (18,19). No activity toward either 2Ј,3Ј-phosphate cyclic mononucleotides, dinucleoside monophosphates, or double-stranded RNA was detected (20).…”
Section: Human Eosinophil Cationic Protein (Ecp)mentioning
confidence: 99%
“…This protein potently elicits neovascularization (Fett et al, 1985;Strydom et al, 1985), induccs second-messenger responses in cultured endothelial cells Vallee, 1988, 1989), and interacts with putative cell-surface receptors (Hu et al, 1991;Badet et al, 1989;Chainoux et al, 1991 ). Eosinophil-derived neurotoxin (EDN) and eosinophil cationic protein (ECP) are also ribonucleases, homologous to pancreatic RNase Beintema et al, 1988b;Rosenberg et al, 1989b;Hamann et al, 1989;Barker el al., 1989;Slifman et al, 3986;Gullberg et al, 1986;Sorrentino and Glitz, 1991), that in this case act as neurotoxins and/or helminthotoxins (Durack et al, 1981 ;Fredens et al, 1982;McLaren et a]., 1984;Sorrentino et al, 1992). It is now apparent through these and other studies (Beintema et al, 1988b) that the human RNases with known sequences can be classified into four types as follows: (a) secretory/ pancreatic, (b) the so-called non-secretory (EDN), (c) ECP and (d) angiogenin.…”
mentioning
confidence: 99%
“…These granule proteins appear to provide effector functions independent of their associated ribonuclease activities. ECP is toxic to mammalian cells and has demonstrable bactericidal and anti-helminthic activities (19)(20)(21)(22)(23), yet its associated ribonuclease activity is relatively weak (15,24). In contrast, EDN has little generalized toxicity (19,20) but is an efficient ribonuclease having activity similar to pancreatic RNase A (24)(25)(26).…”
mentioning
confidence: 99%